A Slow, Not Swift, Battle of the Books: Christian Literature in Nineteenth-Century India - Shaw, Graham (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2015)
This essay examines the preparation, distribution, and reception of Christian literature in nineteenth-century India. To the missionaries, the contemporary publishing landscape lacked any moral content. The output of Indian-owned presses, dominated by religious works, was contemptible; the popular literature imported from Europe deplored; and “infidel” works feared for their potential to turn Indians against all religion. To battle all this, the urgency to prepare a “moral” literature was at the heart of the evangelical project. Indian Christian works ranged from Bible translation into regional languages to all kinds of “support” literature. Various channels were used to distribute this literature, both individual and institutional. Counter-attacks were mounted by India’s own religious communities, turning the missionaries’ own methods against them.